Kemampuan Pemahaman Konsep Matematis Siswa dalam Menyelesaikan Soal pada Relasi dan Fungsi - Melinda Rismawati; Anita Sri Rejeki Hutagaol; Veronika Andau; Yopita Yopita (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2023)
The purpose of this study was to analyze the achievement of each indicator that measures the mathematical understanding ability of high school students in the learning of Relations and Functions. This research is a qualitative descriptive study that seeks to describe students' mathematical understanding abilities. The subjects of this study were 10th Grade students in SMAN 2 Sintang which consisted of 30 students. The data collection method used is a matter of test material relations and functions. Based on the results of the study, it can be concluded that the level of ability of students in high school mathematics subjects is as follows: there is 1 student who scores below 50, there are 3 students who score between 51 and 60, there are 8 students who score between 61 and 70, there are 9 students scored between 71 and 80, there were 9 students who scored 81 and above. The perfect score was achieved by 30 students in the first question number. All partisipants got different results, the first indicator of students getting the fulfillment of the indicator of ability to understand concepts with very good categories, the second indicator of the fulfillment of indicators of understanding ability concept with sufficient category and the third indicator students get the fulfillment of the indicator of ability to understand concepts with very poor category. It can be said that students still have difficulty in solving problems in the form of distinguishing examples from non-examples and solving problems using concepts when solving problems.